Coping strategies of households affected by flooding: A case study of Sekondi-Takoradi Metropolis in Ghana. Issue 5 (28th May 2017) - Danso, Samuel Yaw; Addo, Isaac Yeboah
Abstract: Annually, rivers close to communities within Sekondi-Takoradi Metropolis overflow their banks, especially during the rainy seasons; displacing thousands of residents. Despite this, little is known about the coping strategies used by the residents when flooding occurs. Using mixed method, this article examines the coping strategies employed by households within three communities at risk. Two hundred and seven heads of households residing in Eshiem, Kansawurodo and Whindo were systematically selected to fill in questionnaires, while six key informants comprising chiefs and representatives of flood management institutions were chosen for in-depth interviews. The findings suggest that the commonest coping strategies adopted by residents in all the communities were: temporary vacation of homes, transfer of relevant properties to neighbors and building of flood steps. However, the coping strategies employed by the residents varied by communities, although the majority of them resorted to self-sustaining mechanisms in restoring their losses.